2020
DOI: 10.1111/ahe.12598
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock protein HSP90 immunoexpression in equine endometrium during oestrus, dioestrus and anoestrus

Abstract: Heat shock proteins play a crucial role in cellular development, proliferation, differentiation and apoptosis. Heat shock protein 90 (HSP90) has been localised in the human endometrium, where its immunoexpression changes during the menstrual cycle. Similar studies have not been done for the equid species, so the present study aimed to describe endometrial HSP90 immunoexpression in mare endometrium. Endometrial biopsies were formalin‐fixed and paraffin‐embedded, and sections were stained with haematoxylin–eosin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Previous protocols for the histological assessment of the endometrium employed additional staining with the p16 antibody to differentiate epithelial and stromal cell compartments by selectively staining only epithelial cells 20 , 21 and using traditional image analysis software, which requires pre-processing steps, such as converting original images into grayscale or binary images for detecting staining intensity. 20 , 22 These measurements were limited to specifically chosen tissue areas, 23 , 24 and intra- and inter-observer variability was not considered. 23 In contrast, here we showed that our AI model, which does not require additional staining or image conversion processes, analyzes a whole scanned slide within 1 min while producing highly accurate and reproducible results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous protocols for the histological assessment of the endometrium employed additional staining with the p16 antibody to differentiate epithelial and stromal cell compartments by selectively staining only epithelial cells 20 , 21 and using traditional image analysis software, which requires pre-processing steps, such as converting original images into grayscale or binary images for detecting staining intensity. 20 , 22 These measurements were limited to specifically chosen tissue areas, 23 , 24 and intra- and inter-observer variability was not considered. 23 In contrast, here we showed that our AI model, which does not require additional staining or image conversion processes, analyzes a whole scanned slide within 1 min while producing highly accurate and reproducible results.…”
Section: Discussionmentioning
confidence: 99%
“… 20 , 22 These measurements were limited to specifically chosen tissue areas, 23 , 24 and intra- and inter-observer variability was not considered. 23 In contrast, here we showed that our AI model, which does not require additional staining or image conversion processes, analyzes a whole scanned slide within 1 min while producing highly accurate and reproducible results. The AI algorithm, the functionality and reliability of which were validated in our previous study, 14 coincided with the pathologists’ assessment.…”
Section: Discussionmentioning
confidence: 99%